2015
DOI: 10.1177/1753944715621000
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of blood pressure in patients with hypertension aged 60–79 years before and after the publication of the 2014 Eighth Joint National Committee report

Abstract: Over 1 year at an academic health system, new recommendations from the JNC 8 did not affect mean BP or number of antihypertensives in older patients with hypertension. A similar investigation after more time or in patients with newly diagnosed hypertension may help determine the full impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A previous study conducted at the same academic health system found no difference in mean BP and the number of antihypertensive agents between a similar cohort of patients aged 60–79 years treated for hypertension 1-year before and 1-year after the JNC 8 report [Fixen et al 2016]. Of note, patients in the previous study had an existing diagnosis of hypertension and were currently receiving antihypertensive therapy.…”
Section: Discussionmentioning
confidence: 83%
“…A previous study conducted at the same academic health system found no difference in mean BP and the number of antihypertensive agents between a similar cohort of patients aged 60–79 years treated for hypertension 1-year before and 1-year after the JNC 8 report [Fixen et al 2016]. Of note, patients in the previous study had an existing diagnosis of hypertension and were currently receiving antihypertensive therapy.…”
Section: Discussionmentioning
confidence: 83%